nvestigating the relationship between demographic characteristics and professional competence in dental students of Babol University of Medical Sciences - Fateme Hejrati; Maryam Ghaemi; Effat Khodadadi (Babol University of Medical Sciences, 2023)
Background and Objective: Medical education usually begins with teaching basic biomedical sciences and ends with learning in clinical courses. A significant contribution of clinical education programs is essential in shaping the professional abilities of students. The insufficiency of clinical experience during the study period leads to a decrease in the amount of learning, an increase in stress and the fear of being unable to perform clinical tasks. Therefore, this study was conducted with the aim of investigating the ability of students to perform clinical skills by self-assessment method. Methods: The current research was cross-sectional and descriptive. After preparing the list of students, the researcher attended the clinic departments and distributed the questionnaire. After collecting the data, they were analyzed using SPSS (with descriptive indices and independent t-tests, ANOVA and Spearman's correlation coefficient) and P < 0.05 was considered significant. Findings: 71 dental students participated in this research. The number of female students (57.7%) was more than male students (42.3%). Most dental students of Babol University of Medical Sciences (59.2%) rated their ability as high. In this study, the highest level of students' ability was related to extracting milk teeth, and the lowest level of ability was reported in treating patients with systemic problems. Conclusion: Deficiencies in educational experiences are problematic because the quality of children's dental educational experiences is related to the attitude and professional behavior of dentists. Therefore, dentists with more educational experiences are more likely to treat children than dentists with less educational experiences.